Strategic Position of Indonesian Waters in Supporting Global Maritime Trade Flows - Sianipar, Anaya Tarida Uliartha; Siagian, Citra Cahaya Miranda; Silalahi, Verry Albert Jekson Mardame (Jurnal Cakrawala Akademika, 2025)
Indonesia, as the world's largest archipelagic country, has a strategic geographical position between the Indian and Pacific Oceans, making it an important fulcrum in the global maritime logistics system. This research aims to describe the potential, opportunities, and challenges faced by Indonesian waters in supporting global ocean trade flows. The results show that although Indonesia's waters have vital shipping lanes such as the Strait of Malacca that transport about 30% of global trade, various challenges such as inadequate maritime infrastructure and maritime security issues, such as piracy, still hinder trade efficiency. The discussion included the importance of improving the capacity and quality of port infrastructure, strengthening maritime surveillance and patrols, and integrating domestic port networks to improve connectivity. In addition, the application of digital technology in logistics management and international cooperation to improve maritime security was also discussed as a strategic step. The conclusion of this study emphasizes that with the right measures, Indonesia can strengthen its position as a competitive world maritime center and contribute more to the global economy.